If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43z + -1 = 4(13z + -16) Reorder the terms: -1 + 43z = 4(13z + -16) Reorder the terms: -1 + 43z = 4(-16 + 13z) -1 + 43z = (-16 * 4 + 13z * 4) -1 + 43z = (-64 + 52z) Solving -1 + 43z = -64 + 52z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-52z' to each side of the equation. -1 + 43z + -52z = -64 + 52z + -52z Combine like terms: 43z + -52z = -9z -1 + -9z = -64 + 52z + -52z Combine like terms: 52z + -52z = 0 -1 + -9z = -64 + 0 -1 + -9z = -64 Add '1' to each side of the equation. -1 + 1 + -9z = -64 + 1 Combine like terms: -1 + 1 = 0 0 + -9z = -64 + 1 -9z = -64 + 1 Combine like terms: -64 + 1 = -63 -9z = -63 Divide each side by '-9'. z = 7 Simplifying z = 7
| -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 | | 4z=2.5+2.7 | | 27=0.5x(2+7) | | 9-1/2b=5+8/2b | | xx=42 | | 4k^2-13k+3=0 | | 8-(4y-9)=5-5y | | -3x+22/2= |